PENGARUH PEMBELAJARAN BERBASIS PROYEK DENGAN BERBANTUAN INFOGRAFIS TERHADAP KREATIFITAS SISWA KELAS V SDN 1 WARUNGGUNUNG KABUPATEN LEBAK: Penelitian Kuantitatif - Abdurohman; Nulhakim, Lukman; Fatawi, Izzul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Abstract This study aims to determine the digital literacy skills between experimental student groups who received Project Based Learning (PjBL) treatment assisted by infographic media and students who received discovery learning. This study uses a quantitative approach with a quasi-experimental method and a randomized pretest-posttest control group design. The population and sample in this study were fifth grade students at SDN 1 Warunggunung consisting of two classes. Using the lottery technique, class V-A with 27 students was obtained as a sample and class V-B as a control class with 27 students. The results of the study obtained: (1) There is an influence on student learning creativity before and after being given the discovery learning model treatment, (2) There is an influence on student learning creativity before and after being given the Project Based Learning (PjBL) model treatment assisted by infographic media, and (3) There is a difference in student learning creativity taught through the application of the Project Based Learning (PjBL) model assisted by digital educational games with students taught through the application of the discovery learning model. Thus, it can be concluded that there is an influence of Project Based Learning (PjBL) assisted by infographic media on the learning creativity of class V students at SDN 1 Warunggunung, Lebak Regency. Keywords: project based learning (PjBL), infographics, learning creativity, discovery learning word)